2016
DOI: 10.3109/13880209.2016.1158285
|View full text |Cite
|
Sign up to set email alerts
|

Myricitrin and bioactive extract ofAlbizia amaraleaves: DNA protection and modulation of fertility and antioxidant-related genes expression

Abstract: Context: Albizia species are reported to exhibit many biological activities including antiovulatory properties in female rats and antispermatogenic and antiandrogenic activities in male rats. Objective: The present study investigates the flavonoids of Albizia amara (Roxb.) B. Boivin (Fabaceae) leaves and evaluates their activity on gene expression of fertility and antioxidant glutathione-S-transferaserelated genes of treated female mice in addition to their effect on DNA damage. Materials and methods: Plant ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…One study revealed severe damage to the seminiferous tubules such as the absence of the germinal epithelium from the wall of seminiferous tubules, reduction in the size of the seminiferous tubules, atrophy of the tubules, expansion of interstitial spaces between seminiferous tubule and vacuolization in the seminiferous tubule in diabetic rats [28]. Concomitant with the present study, it was demonstrated that myricitrin can regulate the fertility along with the ability to protect DNA from cells and damage from oxidative stress as its potential effects [29]. Antioxidant treatment with Nacetyl-L-cysteine has been demonstrated as a testicular apoptotic cell death forbidden by regulation of testicular antioxidant defense under diabetic conditions [5].…”
Section: Discussionsupporting
confidence: 80%
“…One study revealed severe damage to the seminiferous tubules such as the absence of the germinal epithelium from the wall of seminiferous tubules, reduction in the size of the seminiferous tubules, atrophy of the tubules, expansion of interstitial spaces between seminiferous tubule and vacuolization in the seminiferous tubule in diabetic rats [28]. Concomitant with the present study, it was demonstrated that myricitrin can regulate the fertility along with the ability to protect DNA from cells and damage from oxidative stress as its potential effects [29]. Antioxidant treatment with Nacetyl-L-cysteine has been demonstrated as a testicular apoptotic cell death forbidden by regulation of testicular antioxidant defense under diabetic conditions [5].…”
Section: Discussionsupporting
confidence: 80%
“…The sequences of specific primer of the genes used are listed in Table 1. The relative quantification of the target (GLAST, GLT-1 and SNAT3) to the reference (b-actin) was determined by using the 2 ÀDDCT method (Kassem et al 2016).…”
Section: Quantitative Real Time-pcr (Qrt-pcr)mentioning
confidence: 99%
“…Hydroalcoholic fractions of some species have been previously applied for isolation and purification of quercetin ( 98 ): hydro-methanolic (70%) extracts of leaf and aerial part of Albizia amara [ 83 ] and Allium porrum [ 84 ] eluting via methanol and methanol‒water (6:4), respectively, and hydro-ethanolic (50%) extract of sugarcane top part of Saccharum officinarum (eluent: chloroform‒methanol 1:1) [ 53 ]. Furthermore, this aglycone flavonol has been isolated from stem aqueous extract of Bauhinia strychnifolia using methanol as eluent in SLH gel filtration method [ 85 ].…”
Section: Isolation Of Various Flavonoid Classifications By Sephadementioning
confidence: 99%